Navigating Firm–Stakeholder Conflicts of Values: A Deweyan Ethical Perspective - Oldham, Simon; Gay, Paul du; Spence, Laura J. (Business & society, 2025)
Organizational values are intuitively important to business life, yet we know little about what happens when there is a clash of values between businesses and stakeholders. What we do know stems from two often disconnected streams of literature, one which has taken a descriptive empirical approach and another which has valorized a normative theoretical perspective. In contrast, and by means of drawing on the empirically accessible context of the small firm in tandem with Deweyan ethics, this article evidences the process by which values conflict arises and how firms seek to respond via a process of inquiry. Through drawing on pragmatist theorization to bridge this descriptive–normative dualism, insights into the nature of values conflict, including the maintenance of moral habit and the fluidity of “correct” moral responses are outlined.